KEWENANGAN BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN (BPKP) UNTUK PENENTUAN KERUGIAN NEGARA DALAM PENANGANAN TINDAK PIDANA KORUPSI - Suryawan, I Made (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2017)
CORRUPTION Is a very serious global issue and a priority to be immediately eliminated and belonging to extraordinary crime (Extra Ordinary Crime). Combating corruption, however, is not an end in itself, but corruption must be eradicated to achieve the broader goals of creating an effective, efficient and equitable government administration system while enhancing honesty and overall governance integrity. One important element in corruption in accordance with Law Number 31 Year 1999 is the element of loss of the State, which in practice is often a heated debate in the trial between the Legal Counsel and the Public Prosecutor, in particular regarding the certainty of the loss of the State and officials authorized to calculate loss of that State.